THE EFFECT OF PAIRED READING STRATEGY IN READING STUDENTS’ ACHIEVEMENT - Surti Milarisa; Penti Hevina Dewi (Language and Education Journal, 2019)
The aimof the study wasto find out the effect of paired readingstrategy in readingstudents’ achievement of the Eighth Grade Students ofSMPN 1 TelukBayur.The design of this research was quantitativedesign. The subject of the research was the eighth grade students of SMPN 1 TelukBayur. By using purposive sampling, the researchers found a sample in this research. The sample of the research was class VIII Chaving31students which consistedof 17female and 14male students. Reading test in the form of multiple-choice which consisted of 20 questions was used to collect the data. To analyze the data, the researcher applied formula paired sample t-test.Based on the result of paired samples test, the mean scorewas 8.064 , standard error was 1.325, the value of tobtainedwas 6.084, at the significance level of p<0.05 in two-tailed testing and df=30. Since the value of tobtained (6.084) was higher than ttable (2.0423) and pvalue (0.00) was less than αvalue (0.05), it meant that a paired reading strategy helped students learn easily to understand the content of the text